THE EFFECTIVENESS OF CUBING AND PEER REVIEWING TECHNIQUES IN TEACHING WRITING DESCRIPTIVE TEXT TO THE ELEVENTH GRADE STUDENTS AT SMA NEGERI 1 BANYUASIN I - Ratmi Ardian (ELTE Journal (English Languange Teaching and Education), 2019)
AbstractThis study aimed to find out: (1) whether or not cubing technique was significantly effective in improving students’ writing achievement; (2) whether or not peer reviewing technique was significantly effective in improving students’ writing achievement, and (3) whether or not there were significant differences in writing achievements among the students of SMA Negeri 1 Banyuasin I who were taught through the techniques of cubing and peer reviewing. The method of the study was randomized two-group pretest-posttest design. Data were collected through pretest and posttest of writing descriptive text. The results of pretest and posttest were analyzed by using t-test. The population was all the eleventh grade students of SMA Negeri 1 Banyuasin I in the academic year 2017/2018. The sampling technique used was simple random sampling. The samples were 90 eleventh grade students of SMA Negeri 1 Banyuasin I. The results showed that: (1) Cubing technique was significantly effective in improving students’ writing achievement; (2) Peer reviewing technique was significantly effective in improving students’ writing achievement; (3) There were significant differences in writing achievement among the students of SMA Negeri 1 Banyuasin I who were taught through the techniques of cubing and peer reviewing.Keywords: cubing, peer reviewing, writing descriptive text